Revision of the Silurian and Devonian stromatoporoids of Bohemia described by Pocta (1894) - May,A. (Journal of the Czech Geological Society, 1999)
The stromatoporoid fauna of Central Bohemia described by Pocta (1894) is revised. Two species - one of them with two subspecies - come from Silurian strata, the other nine valid species (and two synonyms) come from Lower Devonian strata. For every species, the recent name, the synonyms, the type material, the exact type locality, and a diagnosis is given. Lectotypes are designated for six species. Furthermore, the new species Schistodictyon koneprusiense n. sp. from the Middle Pragian of Koneprusy (Central Bohemia) is described.
Keywords: Stromatoporoidea; taxonomy; Silurian; Devonian; Bohemia